Research on Combined Electricity and Heating System Scheduling Method Considering Multi-Source Ring Heating Network - Ye, Jing; Zhao, Danyang; Zhang, Lei; Li, Zhenghua; Zhang, Tao (Frontiers in Energy Research, 2021)
Heating network constraint is one of the important factors that affect the scale of electro-thermal coupling scheduling. This paper first establishes an electrothermal coupling scheduling model considering the multi-source ring heating network pipe structure, and then proposes a method of simplifying a multi-source cyclic heating network topology approximation. Second the electrothermal coupling scheduling system is coordinated and solved. Finally, Through the simulation example results, the annular heating network topological approximate equivalent can simplify the model complexity of the original heating network, while also retaining the thermal dynamic characteristics of the initial multi-source ring heating network. This study will greatly improve the efficiency of solving the electrothermal coupling system.